Eksplorasi Ragam Penelitian dalam Pengembangan Ilmu Pendidikan Agama Islam - Usmiati, Nevianti Dewi Suyanlis; Aprilia, Siska; Amir, Muh Ikraam Sayyid; Saprin, Saprin; Majid, Jamaluddin (CV. Rayyan Dwi Bharata, 2025)
This article discusses various research approaches in Islamic Religious Education (PAI), including qualitative, quantitative, mixed methods, and research and development (RD) approaches. The purpose of this study is to analyze the contribution of each approach to the development of Islamic education theory and practice. This research was conducted using a literature review method based on relevant national and international journals. The findings indicate that each approach has a unique role, ranging from exploring spiritual values to developing applicable learning media. This study recommends strengthening methodological capacity in PAI research to enhance its relevance and impact on current and future Islamic education.